PERUMUSAN STRATEGI BISNIS UD. BONI JAYA SITUBONDO DENGAN MENGGUNAKAN MODEL MATRIK GENERAL ELECTRIC (GE) - Dinda Estuputri; Indro Herry Mulyanto; Sauptika Kancana (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2019)
Business strategy is an important element that must be owned by business companies so that companies have competitive advantages and can win the competition while maintaining the survival of the company. This is what underlies the researchers to formulate business strategies that can be used by UD. Boni Jaya. In conducting business strategy formulation, researchers used the General Electric (GE) Matrix model. The General Electric (GE) matrix is also commonly referred to as the McKinsey matrix. The General Electric (GE) matrix has two main variables, Industry Attractiveness and Competitive Strength. Both of these variables are based on several indicators. In the Industry Attractiveness variable there are 7 indicators. Then, for the variable Competitive Strength, there are 8 indicators. These indicators are declared valid and valid based on triangulation test through 3 sources, namely observation, interview (in- depth interview), and documentation. The results of the calculation of the General Electric (GE) Matrix, UD. Boni Jaya is in quadrant 2 position, which is